2009
DOI: 10.1016/j.joca.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The chondroprotective effect of selective COX-2 inhibition in osteoarthritis: ex vivo evaluation of human cartilage tissue after in vivo treatment

Abstract: Using this novel approach we were able to demonstrate an in vivo generated chondrobeneficial effect of celecoxib in patients with end stage knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 33 publications
3
55
2
3
Order By: Relevance
“…Our data confirm the possible chondroprotective role of a COX-2 selective inhibitor in agreement with other authors (14,16,24,40,46,47,51,52).…”
Section: Discussionsupporting
confidence: 93%
“…Our data confirm the possible chondroprotective role of a COX-2 selective inhibitor in agreement with other authors (14,16,24,40,46,47,51,52).…”
Section: Discussionsupporting
confidence: 93%
“…We reported the anti-inflammatory role of morin on OA through suppressing inflammatory mediator production. Previous studies showed that some COX-2 selective inhibitors could also inhibit inflammatory cytokine-induced inflammatory response and cartilage damage [6,23]. These results showed that VA694, Naproxcinod and Naproxen could inhibit IL-1β-induced inflammatory response by attenuating NF-κB activation [24].…”
Section: Discussionmentioning
confidence: 84%
“…In a trial (LOE IIb), patients who were candidates for total knee replacement (TKR) surgery were treated either with celecoxib or indomethacin for a four-week period prior to the procedure, and cartilage and synovial samples were evaluated after the surgery. [61] Proteoglycan synthesis was found to be significantly increased among celecoxib users but not in the indomethacin and control groups. Prostaglandin E 2 (PGE 2) levels were found to be lower in the patients who used either of the drugs when compared with the controls.…”
Section: Pharmacologic Treatmentmentioning
confidence: 89%